2008
DOI: 10.1017/s0266467407004725
|View full text |Cite
|
Sign up to set email alerts
|

Variation in longevity and traits of leaves among co-occurring understorey plants in a tropical montane forest

Abstract: Abstract:The relationship between leaf longevity and other leaf traits was compared among different life-form categories (trees, herbs, climbers and epiphytes) of 101 plant species in a tropical montane forest on Mt. Halimun, West Java, Indonesia. We applied the Cox proportional hazards regression to estimate the leaf longevity of each species from 30 mo of census data. We examined whether estimated longevity was explained by either species life-form categories, taxonomic groupings (eudicots, monocots, magnoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Traits included are SLA (leaf area per unit leaf mass, mm 2 mg À1 ), LL (average lifespan of leaves, in months), leaf nitrogen content per leaf area (N area , mg g À1 ), maximum carboxylation rate of Rubisco enzyme per leaf area (v cmaxarea , lmol CO 2 m À2 s À1 ), and WD (wood dry mass per unit of green volume, g cm À3 ). All TRY data we used relates to the following original references: (Cornelissen, 1996;Cornelissen et al, 1996Cornelissen et al, , 2003Cornelissen et al, , 2004Castro-Diez et al, 1998;Atkin et al, 1999;Medlyn et al, 1999;Fonseca et al, 2000;Niinemets, 2001;Shipley, 2002;Shipley & Vu, 2002;Loveys et al, 2003;Ogaya & Penuelas, 2003;Quested et al, 2003;Xu & Baldocchi, 2003;Diaz et al, 2004;Wright et al, 2004Wright et al, , 2007Wright et al, , 2010Preston et al, 2006;Campbell et al, 2007;Garnier et al, 2007;Swaine, 2007;Cornwell et al, 2008;Kleyer et al, 2008;Kurokawa & Nakashizuka, 2008;Reich et al, 2008Reich et al, , 2009Shiodera et al, 2008;Chave et al, 2009;Fyllas et al, 2009;Kattge et al, 2009;Poorter et al, 2009;Freschet et al, 2010;Laughlin et al, 2010;Messier et al, 2010;Ordonez et al, 2010;…”
Section: Tree Establishmentmentioning
confidence: 99%
“…Traits included are SLA (leaf area per unit leaf mass, mm 2 mg À1 ), LL (average lifespan of leaves, in months), leaf nitrogen content per leaf area (N area , mg g À1 ), maximum carboxylation rate of Rubisco enzyme per leaf area (v cmaxarea , lmol CO 2 m À2 s À1 ), and WD (wood dry mass per unit of green volume, g cm À3 ). All TRY data we used relates to the following original references: (Cornelissen, 1996;Cornelissen et al, 1996Cornelissen et al, , 2003Cornelissen et al, , 2004Castro-Diez et al, 1998;Atkin et al, 1999;Medlyn et al, 1999;Fonseca et al, 2000;Niinemets, 2001;Shipley, 2002;Shipley & Vu, 2002;Loveys et al, 2003;Ogaya & Penuelas, 2003;Quested et al, 2003;Xu & Baldocchi, 2003;Diaz et al, 2004;Wright et al, 2004Wright et al, , 2007Wright et al, , 2010Preston et al, 2006;Campbell et al, 2007;Garnier et al, 2007;Swaine, 2007;Cornwell et al, 2008;Kleyer et al, 2008;Kurokawa & Nakashizuka, 2008;Reich et al, 2008Reich et al, , 2009Shiodera et al, 2008;Chave et al, 2009;Fyllas et al, 2009;Kattge et al, 2009;Poorter et al, 2009;Freschet et al, 2010;Laughlin et al, 2010;Messier et al, 2010;Ordonez et al, 2010;…”
Section: Tree Establishmentmentioning
confidence: 99%
“…The extensive compilation of leaf longevities used in the review paper by Wright et al (2005 a ) included very few climbers; however, it suggested a similar mean longevity for lianas and erect woody species. Similarly, a survey of leaf longevities in tropical understorey species in Indonesia showed both large variability and lack of consistent differences between growth forms in spite of a lower LMA in climbers ( Shiodera et al , 2008 ). The latter authors suggest that the uncoupling of LMA and longevity relationship in lianas can be attributed to a lower requirement for leaf lamina support in semi-epiphytic climbers.…”
Section: Leaf Characteristicsmentioning
confidence: 99%
“…; Reich et al . ; Vincent ; Shiodera, Rahajoe & Kohyama ). Then, which of the cases appropriately reflects the pattern for real leaves?…”
Section: Variation In Lls As a Factor Affecting Estimation Biasmentioning
confidence: 99%
“…However, LLS varies within a leaf cohort in a wide variety of plant species, as indicated by the shape of leaf survivorship curves (e.g. Bazzaz & Harper 1977;Maillette 1982;Nilsen 1986;Lowman 1992;Osada et al 2003;Reich et al 2004;Vincent 2006;Shiodera, Rahajoe & Kohyama 2008). Then, which of the cases appropriately reflects the pattern for real leaves?…”
Section: Daily Carbon Gainmentioning
confidence: 99%